2009
DOI: 10.1007/s00221-009-2087-8
|View full text |Cite
|
Sign up to set email alerts
|

Open-loop, closed-loop and compensatory control: performance improvement under pressure in a rhythmic task

Abstract: According to explicit monitoring theories, the phenomenon of choking under pressure is due to actors focusing their attention on the execution of the skill. This step-by-step perceptually guided control may then interfere with automatic execution. In order to examine the changes in control at the sensorimotor level, we examined the rhythmic task of ball bouncing which affords detailed quantification of indicators of control based on previous research. The hypothesis was that under psychological pressure percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…For example, DeCaro et al (2011) argue that in Beilock et al's (2006) golf putting task and in Chalabaev et al's (2008) soccer dribbling task expert performance was debilitated because stereotype threat led these participants to monitor their well-learned behaviors. However, in Ehrlenspiel et al (2010) and in Experiment 3 of the current research, participants had learned to perform the task, which facilitated, not debilitated performance. Ehrlenspiel et al (2010) suggested that this facilitated performance of their threatened participants may have been the result of the rhythmic nature of the task, which might make it less susceptible to the effects of explicit monitoring.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…For example, DeCaro et al (2011) argue that in Beilock et al's (2006) golf putting task and in Chalabaev et al's (2008) soccer dribbling task expert performance was debilitated because stereotype threat led these participants to monitor their well-learned behaviors. However, in Ehrlenspiel et al (2010) and in Experiment 3 of the current research, participants had learned to perform the task, which facilitated, not debilitated performance. Ehrlenspiel et al (2010) suggested that this facilitated performance of their threatened participants may have been the result of the rhythmic nature of the task, which might make it less susceptible to the effects of explicit monitoring.…”
Section: Discussionmentioning
confidence: 69%
“…The participants then performed another 32 trials of the task. Ehrlenspiel et al (2010) found that the participants subject to performance pressure improved more from day 1 to day 2 than participants in the control group. This finding is consistent with the mere effort account in that the participants learned to perform the task on day 1.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Based on the observation that focusing attention on automatized tasks frequently decreases performance (referred to as choking; see Ehrlenspiel, Wei, & Sternad, 2010;Koedijker & Mann, 2015), it was hypothesized, as assessed by operational control metrics, that driving performance would be less variable while mind wandering than alert. Specifically, it was expected that speed variability, lane deviation, lateral position variability and steering reversal rate would be lower when mind wandering.…”
Section: Objectivesmentioning
confidence: 99%